2017
DOI: 10.1016/j.ymgmr.2017.04.004
|View full text |Cite
|
Sign up to set email alerts
|

Albuterol as an adjunctive treatment to enzyme replacement therapy in infantile-onset Pompe disease

Abstract: BackgroundEarly initiation of enzyme replacement therapy (ERT) with recombinant human acid alpha-glucosidase is an effective treatment for patients with infantile-onset Pompe disease (IOPD) but cannot prevent a slow progression of myopathy. Albuterol has been shown to be helpful in adult patients with Pompe disease, and therefore, we administered an open-label adjunctive therapy with albuterol in IOPD patients undergoing ERT.MethodsFourteen patients, aged 2 to 12 years, were enrolled in this study; all of them… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 22 publications
1
3
0
Order By: Relevance
“…This suggests that the improved grip strength in salbutamol treated ColQ −/− animals cannot be readily explained by an anabolic effect on skeletal muscle. This is consistent with the lack of evidence of clinical benefit of sympathomimetic treatment in myopathies and muscular dystrophies (20,21,66,67). Since both the structure and function of the NMJs is abnormal in ColQ −/− mice (34), we turned our attention to the possibility that salbutamol may act to enhance muscle activation by action on the NMJs.…”
Section: Discussionsupporting
confidence: 84%
“…This suggests that the improved grip strength in salbutamol treated ColQ −/− animals cannot be readily explained by an anabolic effect on skeletal muscle. This is consistent with the lack of evidence of clinical benefit of sympathomimetic treatment in myopathies and muscular dystrophies (20,21,66,67). Since both the structure and function of the NMJs is abnormal in ColQ −/− mice (34), we turned our attention to the possibility that salbutamol may act to enhance muscle activation by action on the NMJs.…”
Section: Discussionsupporting
confidence: 84%
“…For GSD III, a high protein diet has been reported to improve cardiomyopathy [90]. Recently, it has been shown that albuterol could be an adjunctive therapy for patients with EOPD, although the overall benefit seems to be limited [91].…”
Section: Carbohydrate Metabolismmentioning
confidence: 99%
“…Hearing loss is also documented and may further impact speech [48] but does not fully explain the degree of speech impairment observed in affected patients [46]. Early diagnosis with early initiation of ERT [49], high-dose regimens of ERT [3,50], and adjunctive treatments like physical therapy and beta-2 adrenergic agonists [51] often result in improvements or stabilization of motor and pulmonary function. However, dysarthria frequently appears to remain.…”
Section: Discussionmentioning
confidence: 99%